Examining internet use for health information seeking and influencing factors among undergraduate health science students in Southwest Ethiopia - Alex Ayenew Chereka; Fikadu Wake Butta; Addisalem Workie Demsash; Sisay Yitayh Kassie; Adamu Ambachew Shibabaw; Abiy Tasew Dubale; Geleta Nenko Dube; Mekonnen Kenate Hunde; Wubalem Dilie Limeneh; Amare Dagnew Fentahun; Milkias Dugassa Emanu; Mekashaw Tareke Abebe; et al. (Heliyon)
Background: The Internet has become a pivotal resource for accessing health information globally, offering unprecedented convenience and breadth of resources. This cross-sectional study examines the implications of Internet use for health information seeking and the influencing factors among undergraduate health science students in Southwest Ethiopia. Methods: An institutional-based cross-sectional study was conducted from November 10 to December 10, 2023. The study enrolled 423 students. Data were collected using a pretested and structured self-administered questionnaire. Data entry and analysis were performed using EpiData V4.6 and STATA V17, respectively. Bi-variable and multivariable logistic regression analyses were conducted to identify factors associated with the outcome variable. Statistical significance was determined using a P-value of less than 0.05. Result: A total of 423 respondents participated in this study, resulting in a 100 % response rate. Among them, 67.4 % (95 % CI: 63.0%–72.0 %) reported using the Internet for health purposes. Factors significantly associated with this usage included being a third-year student or above (AOR = 2.33, 95 % CI: 1.36–3.99), owning a smartphone (AOR = 2.41, 95 % CI: 1.14–5.10), having good awareness (AOR = 2.81, 95 % CI: 1.55–5.09), holding a favorable attitude (AOR = 9.58, 95 % CI: 5.10–18.00), and possessing adequate e-health literacy (AOR = 5.25, 95 % CI: 2.89–9.46). Conclusion: This study underscores the internet's primary role in accessing information on diseases, treatments, healthy lifestyles, and prevention. Key factors such as e-health literacy, attitude, awareness, smartphone usage, and study timing significantly influence this trend. Understanding these factors is vital for optimizing internet resources for health information dissemination.